1996
DOI: 10.1080/00222895.1996.9941732
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between Breathing and Finger Tracking in Man

Abstract: Arm and leg movements are known to produce temporal pattern changes of breathing. This can be interpreted as coordination, as defined by von Holst (1939). The aim of the present study was to find whether breathing exerts an influence in a reverse direction on a nonrespiratory movement as well. A pursuit tracking test was used, and test individuals (N = 19) were instructed to track a visually presented step function by flexion or extension of their right index finger. Velocity and precision of the step response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Motor activity can cause modulations of the time course of respiration which are mediated by interactions in the central nervous system even when entrainment or rhythmical coordination (as de®ned by von Holst 1939) is not present (Hill et al 1988;Perse gol et al 1988;Raûler et al 1996). The reduction of t tot [S A 1] during the tracking tests compared to breathing at rest (see Table 1) and of t tot [S] compared to control breaths (see Fig.…”
Section: Movement-induced Changes Of the Respiratory Patternmentioning
confidence: 94%
See 1 more Smart Citation
“…Motor activity can cause modulations of the time course of respiration which are mediated by interactions in the central nervous system even when entrainment or rhythmical coordination (as de®ned by von Holst 1939) is not present (Hill et al 1988;Perse gol et al 1988;Raûler et al 1996). The reduction of t tot [S A 1] during the tracking tests compared to breathing at rest (see Table 1) and of t tot [S] compared to control breaths (see Fig.…”
Section: Movement-induced Changes Of the Respiratory Patternmentioning
confidence: 94%
“…Very few experiments have given evidence of eects of breathing on simultaneous motor activities (Perse gol et al 1988;Viala 1986;Raûler et al 1990Raûler et al ,1996Raûler and Kohl 1996a).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, evidence suggests coupling improves breathing efficiency in some circumstances [2], [15], [24]. On the other hand, humans also couple breathing frequency with low impact, non-locomotor movements such as finger and arm tracking [25], [26]. Thus, large mechanical interactions are not required to induce rhythmic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, for example, phase-locking with respiration has been observed for visual signal detection (Flexman et al, 1974) eye movements (Rittweger and Pöpel, 1998; Rassler and Raabe, 2003), the temporal grouping of pianistic finger movements (Ebert et al, 2002), reaction time to visual (Li et al, 2012) and auditory (Gallego et al, 1991) stimuli, and grip-force (Li and Laskin, 2006). Rassler et al (1996) reported that response latency, tracking-precision and movement duration of finger movements made to track a visual target showed significant respiratory-phase-dependent differences and that the respiratory-phase-dependence differed between finger flexion and extension movements (Rassler, 2000). In mice, movements of the mystacial whiskers are phase-locked to respiration (Cao et al, 2012; Moore et al, 2013).…”
mentioning
confidence: 99%